(untitled) (Research, Society and Development, 2023)
Introduction: Domestic violence has been endemic in the country and around the world, being aggravated by the COVID-19 pandemic. This is because restrictive social measures were imposed and many women were forced into confinement with violent partners, resulting in an increase in complaints. Objective: To analyze the incidence of domestic violence during the pandemic in Brazil, through a literature review. Methodology: The research was carried out in May 2023, 160 articles were found in the databases, 13 of which were selected. Results: From the results found, it was possible to observe that during the COVID-19 pandemic, there was a significant increase in complaints of domestic violence in the country, highlighting the period when social isolation began. The most prevalent victims of the incidents were women, highlighting not only cases of psychological and physical violence, but also an increase in cases of femicide. Studies also highlighted flaws in the network to combat violence against women. Conclusion: During the COVID-19 pandemic, cases of domestic violence in the country increased. This type of aggression is a serious public health problem, making greater efforts necessary to reduce this social issue.